The Effect Of Transformational Leadership And Green Human Resources Management On Competitive Advantage Mediated By Self-Efficacy And Employee Loyalty - Cut Andriani Zulkarnain; Retno Purwani Setyaningrum; Anna Wulandari (UNIVED Press, 2024)
This study aims to determine the effect of Transformational Leadership and Green Human Resources Management on Competitive Advantage mediated by Self-Efficacy and Employee Loyalty at Fnb Companies in Bekasi Regency. Respondents of this study were 96 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that (1) Transformational Leadership affects Competitive Advantage in Food and Beverage Companies in Bekasi Regency, (2) Green Human Resources Management has no effect on Competitive Advantage in Food and Beverage Companies in Bekasi Regency, (3) Transformational Leadership affects Employee Loyalty in Food and Beverage Companies in Bekasi Regency, (4) Green Human Resources Management affects Self-Efficacy in Food and Beverage Companies in Bekasi Regency, (5) Self-Efficacy affects Competitive Advantage in Food and Beverage Companies in Bekasi Regency, (6) Employee Loyalty affects Competitive Advantage at Food and Beverage Companies in Bekasi Regency, (7) Self-Efficacy affects Employee Loyalty at Food and Beverage Companies in Bekasi Regency, (8) Employee Loyalty as a mediating variable has a role in weakening the effect of Transformational Leadership on Competitive Advantage at Food and Beverage Companies in Bekasi Regency, (9) Self-Efficacy as a mediating variable has a role in strengthening the effect of Green Human Resources Management on Competitive Advantage at Food and Beverage Companies in Bekasi Regency.